Online Higher Education in Bangladesh during Covid-19: Its Challenges and Prospects - Chowdhury, Md Khaled; Behak, Fariza Binti Puteh (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2022)
Online higher education in Bangladesh has not gained expected popularity and a switch to it has always been seen as a challenge despite its potentials here. So, our research investigates the challenges in implementing online higher education and prospects for this for Bangladeshi universities. To do this we have explored the background and evolution of e-learning and online learning in Bangladeshi higher education and the potentials that it might offer in this area. This is a study which may also be called a systematic review. This study reviews research publications on the topic that were published during the last ten years. The research publications include fourteen newspaper articles, twenty two journal articles, four doctoral theses, four reports, three conference proceedings and nine websites. The study finds out that there are a number of problems in implementing online higher education such as, negative perception of teachers, parents and students about the online education, digital divide in the country. On the other hand, online or at least the blended education can be a good alternative to face-to-face higher education of Bangladesh that faces a number of constraints such as, crisis of seats and reputed higher education institutes, session backlog, cost of higher education in universities as well as the conducive factors such as, digitalization, digital literacy, widespread use of mobile phone and the internet. This study recommends that blended courses and programs may be offered in higher education of Bangladesh considering the prospects it offers to our higher education providers .